KAJIAN PENGGUNAAN RUMPUT LAUT Eucheuma spinosum SEBAGAI BAHAN PENGISI TERHADAP SIFAT KIMIA, FISIK DAN SENSORI ES KRIM - Djelantik, Ni Putu Astrinia; Suter, I Ketut; Sugitha, I Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2016)
The purposes of this research were to know the effect of the using of  seaweed Eucheuma spinosum and the best concentration as a filler to the chemical, physical and sensory ice cream. The Randomized Block Design (RBD) were used to evaluate the research with five treatments of E. spinosum concentration such as: 0, 5, 10, 15 dan 20% and three replications to obtain 15 units experiment. The variables measured were fat, protein, ash, crude fiber content, melting resistance, aroma, texture, color, flavor and overall acceptance. The data were analyzed by SPSS 17 th version and if there was impact on the treatments , it would be followed by Duncan Multiple Range Test (DMRT). The results showed that E. spinosum were significantly effect to the chemical, physical and sensory ice cream. It could be concluded that the best result was obtained by using 10% of E. spinosum with the characteristics of 12,39% fat, 2,42% protein, 0,59% ash, 18,34% crude fiber, melting resistance of 367 seconds or 6 minutes 12 seconds, colour 4,1 (yellowish white), texture 3,5 (soft), aroma 3,9 (typical little milk), taste 5,5 (like) and 5,6 overall acceptance (like).
Keywords: Eucheuma spinosum, Ice cream